Serum microRNA-126 expression as a biomarker of diabetic retinopathy - Ni Made Ayu Surasmiati; Ni Made Ari Suryathi; Ari Andayani (Universa Medicina, 2023)
BackgroundDiabetic retinopathy (DR) is a microvascular complication of diabetes mellitus (DM). Diabetic retinopathy causes permanent blindness in the productive age group and has a multifactorial pathogenesis. MicroRNA-126 (miRNA-126) regulates the expression of the vascular endothelial growth factor (VEGF) gene at the post-transcriptional level, VEGF being an important angiogenic protein regulating inflammation in DR development. This study aimed to determine serum miRNA-126 expression as a biomarker in DM patients with DR. MethodsThis was a cross-sectional study involving 4 healthy persons and 21 type 2 DM patients. Subjects consisted of 4 groups: i) healthy controls, ii) DM patients without diabetic retinopathy (NDR), iii) DM patients with non-proliferative DR (NPDR) and iv) DM patients with proliferative DR (PDR). Venous blood was collected from subjects for miRNA-126 examination by real-time polymerase chain reaction (PCR). MiRNA-126 in each group was analyzed using the One Way Anova test and p<0.05 was considered to be statistically significant. ResultsMean miRNA-126 expression was significantly decreased in PDR (1.86±1.03) and NPDR (1.01±0.43 ) groups when compared to healthy control (2.44±1.29) and NDR groups (2.15± 0.48) (p=0.027). MiRNA-126 values of less than 1.81 can differentiate NDR from the control group (sensitivity 83%, specificity 75%) and miRNA-126 of less than 1.56 can be used to predict NPDR when compared to the control group (sensitivity 86%, specificity 75%). ConclusionSerum miRNA-126 is a potential biomarker for screening of NPDR and NDR in type 2 DM patients, and could be considered a non-invasive diagnostic parameter.